Low‐Temperature Cationic Rearrangement in a Bulk Metal Oxide. Issue 34 (20th May 2016) - Li, Man‐Rong; Retuerto, Maria; Stephens, Peter W.; Croft, Mark; Sheptyakov, Denis; Pomjakushin, Vladimir; Deng, Zheng; Akamatsu, Hirofumi; Gopalan, Venkatraman; Sánchez‐Benítez, Javier; Saouma, Felix O.; Jang, Joon I.; et al.
Abstract: Cationic rearrangement is a compelling strategy for producing desirable physical properties by atomic‐scale manipulation. However, activating ionic diffusion typically requires high temperature, and in some cases also high pressure in bulk oxide materials. Herein, we present the cationic rearrangement in bulk Mn2 FeMoO6 at unparalleled low temperatures of 150–300  o C. The irreversible ionic motion at ambient pressure, as evidenced by real‐time powder synchrotron X‐ray and neutron diffraction, and second harmonic generation, leads to a transition from a Ni3 TeO6 –type to an ordered‐ilmenite structure, and dramatic changes of the electrical and magnetic properties. This work demonstrates a remarkable cationic rearrangement, with corresponding large changes in the physical properties in a bulk oxide at unprecedented low temperatures. Abstract : The unprecedented low‐temperature (150–300 °C) cationic rearrangement in bulk Mn2 FeMoO6 leads to a transition from a Ni3 TeO6 ‐type to an ordered‐ilmenite structure, and dramatic changes of the electrical and magnetic properties, which demonstrates remarkable physical property tunneling through atomic‐scale manipulation in bulk oxide under mild conditions.